2017
DOI: 10.1002/cctc.201701436
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyst‐free, Visible Light Driven, Gold Promoted Suzuki Synthesis of (Hetero)biaryls

Abstract: A visible‐light driven Suzuki cross‐coupling reaction was performed with colored and bench‐stable arylazosulfones in the presence of Ph3PAuCl (5 mol %) as the catalyst. The absence of a photocatalyst, along with the use of commercially available and easy‐to‐handle arylboronic acids underline the novelty and synthetic usefulness of the protocol. A reaction mechanism involving the generation of an aryl radical as the key intermediate has been proposed on the basis of experimental investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 44 publications
1
45
0
1
Order By: Relevance
“…Then, the alkyne substrate is activated by the Au III intermediate. [290] Chem. The catalytic cycle is similart othat proposed earlierf or the dual Au and photoredox catalysis occurring in the presenceo faphotocatalyst.S auer et al in another study, reported photosensitizer-free, Au-and photoredox-mediated Suzuki cross-coupling reactions between aryl boronic acids and aryl diazonium salts (Scheme 58 a).…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the alkyne substrate is activated by the Au III intermediate. [290] Chem. The catalytic cycle is similart othat proposed earlierf or the dual Au and photoredox catalysis occurring in the presenceo faphotocatalyst.S auer et al in another study, reported photosensitizer-free, Au-and photoredox-mediated Suzuki cross-coupling reactions between aryl boronic acids and aryl diazonium salts (Scheme 58 a).…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…(a) Dual Au and visible-light-promoted Suzuki coupling reaction for the selective synthesis of hetero-biaryls. [290] Chem. Eur.J.2020, 26, www.chemeurj.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim state.…”
Section: Dual Gold and Photoredox Catalysisf Or Cross-couplingr Eactionsmentioning
confidence: 99%
“…As an alternative to aryldiazonium salts, Protto and Bandini et al have developed a cross-coupling reaction between arylboronic acids and arylazosulfones that takes place under photocatalyst-free conditions (Scheme 21). 38 Under light irradiation, the photolabile arylazosulfones fragment into an aryl radical and a methanesulfonyl radical. The authors propose that after addition of the aryl radical to gold(I), the generated gold(II) intermediate is oxidized to gold(III) by the methanesulfonyl radical.…”
Section: Scheme 20 Cross-coupling Between Arylboronic Acids and Aryldmentioning
confidence: 99%
“…Indeed, the irradiation with visible light of an arylazo sulfone in polar solvents resulted in the homolytic cleavage of the S–N bond, with the subsequent formation of the corresponding aryl radical. Such behavior has been exploited in the preparation of aromatic amides [38], allylarenes [39], triarylethylenes [40], as well as in the photocatalyst-free, gold catalyzed Suzuki coupling to biaryls [41]. We reasoned that such substrates could be employed in the development of a photocatalyst-free, visible-light driven hydro/deutero deamination process exploiting the well-known hydrogen atom abstraction capability of aryl radicals (Ar • , Scheme 1d), as detailed below.…”
Section: Introductionmentioning
confidence: 99%